Combined Treatment With Leuprolide Acetate and Burosumab in X-linked Hypophosphatemia and Precocious Puberty: A Therapeutic Response - Gustavo Tempone Cardoso Penna, MS; Carolina Costa Figueiredo, MD, MSc; Nara Michelle de Araújo Evangelista, MD, MSc; Vânia de Fátima Tonetto Fernandes, MD, PhD; Patricia Salmona, MD; Guido de Paula Colares Neto, MD, PhD (AACE Clinical Case Reports)
Background/Objective: Individuals with X-linked hypophosphatemia (XLH) generally experience normal puberty. However, the prevalence of central precocious puberty (CPP) in patients with XLH seems to be similar to that of the general population, and CPP may similarly impact their predicted final height. Case Report: A female patient was diagnosed with XLH at 3 years old and received regular calcitriol and sodium-potassium phosphate treatment until age six. During this period, she showed increased growth velocity and improved height Z-score (from −2.38 SD to −1.95 SD). At 6 years and 11 months, she was diagnosed with idiopathic CPP, marked by thelarche, a growth spurt, and advanced bone age, resulting in a decreased predicted final height Z-score. She began pubertal blockade with leuprolide acetate and transitioned from conventional XLH treatment to burosumab. The combination of these treatments led to stabilized bone age, normalized growth velocity, and improved final height prediction without side effects or negative impacts on bone health during treatment. Discussion: Although the prevalence of CPP in XLH patients has not been extensively studied, CPP in XLH may affect final height and worsen rickets by increasing mineral demands during growth spurts. Thus, CPP can be treated in patients with XLH, who may have compromised height outcomes, using synthetic gonadotropin-releasing hormone analogs. Conclusion: In the described XLH patient with CPP, the combined use of gonadotropin-releasing hormone analogs and burosumab was a safe strategy to stabilize pubertal progression and bone age, minimize anthropometric loss, and avoid exacerbating bone deformities.